The Role of Midwives and Information Media in Knowledge, Attitude, and Behavior of Postpartum Mothers about COVID-19 Health Protocol - Ratih Kusuma Wardhani; Eva Nur Azizah; Luluk Susiloningtyas (Global Medical & Health Communication (GMHC), 2022)
Transmission of COVID-19 in pregnant women and postpartum mothers is potentially high risk. Postpartum mothers implement health protocols influenced by predisposing, enabling, and need factors. This study aimed to analyze the role of midwives and information media in postpartum mothers' knowledge, attitude, and behavior regarding the COVID-19 health protocol. This research was conducted in RSUD Kabupaten Kediri, in August–October 2021. The study used a correlational analytic method. The sample was postpartum mothers using a simple random sampling technique where 100 respondents included in inclusion criteria were given a questionnaire to complete. This study employed Kendall's tau correlation test to analyze the data. The result showed that the role of midwives is mainly in the good category (66%) while the media information is also in the good category (58%). Most of the respondents had sufficient knowledge (37%), the attitude of respondents in implementing the COVID-19 health protocol had a positive category (52%), and the behavior of the respondents mostly had a good category (54%). This study concludes that there is a significant correlation between the role of midwives to knowledge (p=0.009), attitudes (p=0.003), and behavior (p=0.000) of postpartum mothers. There is a significant correlation between information media and knowledge (p=0.042) and behavior (p=0.012) of postpartum mothers. However, there is no significant correlation between information media and the attitude (p=0.756) of postpartum mothers regarding the COVID-19 health protocol.